STUDI KOMPARASI EFEKTIVITAS PENGGUNAAN BEBERAPA SENYAWA NATRIUM SEBAGAI ZAT BANTU DALAM PROSES PELEPASAN MALAM PADA BATIK TULIS - Maghfiroh Maghfiroh; Nella Sari (LPPM Universitas Pekalongan, 2017)
The use of sodium compounds are sodium carbonate, sodium silicate, sodium chloride andsodium hydroxide as auxiliary agent in the malam releasing process in batik was investigated. Thisstudy aims to determine the effectiveness of these sodium compounds for the malam releasingprocess and know the factors that influence the effectiveness of the auxiliary in the process. Thisstudy used an experimental method with 5 treatments and 3 repetition that treatment A (withoutauxiliray agent), B (sodium carbonate), C (sodium silicate), D (sodium chloride), and E (sodiumhydroxide). The level of effectiveness is measured by the percentage of the malam release of thecotton fabric. The testing process is done by successively making designs on cotton fabric, then themalam sticking process, the coloring process, and the malam releasing process. The malam releasingprocess do with each using auxiliary agent sodium carbonate, sodium silicate, sodium chloride,sodium hydroxide and one sample without auxiliary substances are used as controls. The resultsshowed that the use of auxiliary from sodium compounds can simplify the malam releasing process.Sodium compounds that most effective to be used in the malam releasing process was sodiumsilicate followed by sodium carbonate, sodium chloride, and sodium hydroxide. The most effectivein the malam releasing process in batik cotton fabric was sodium silicate. This was because theamount of sodium unsure in the sodium silicate compounds most numerous and the bonding ofsodium and silicate was weakest among other sodium compounds used in this study.